PENGEMBANGAN E-MODUL AJAR BERBASIS FLIPBOOK PADA MATA KULIAH PROGRAM PENGEMBANGAN KELOMPOK BERMAIN ANAK USIA DINI: PENGEMBANGAN E-MODUL AJAR BERBASIS FLIPBOOK PADA MATA KULIAH PROGRAM PENGEMBANGAN KELOMPOK BERMAIN ANAK USIA DINI - Ningsih, Sulastya; Nuraini, Febritesna; Hardiyanti, Waode Eti; Setiyowati, Endah (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2024)
Increasing student knowledge requires the availability of adequate learning resources to support the learning process. The development of kvisoft flipbook-based teaching materials is one of the important components to attract students' attention, is easy to understand and can be accessed anywhere so that students can study independently and get good quality learning outcomes. The purpose of this research is to determine the design process for developing flipbook-based e-modules, the feasibility of e-modules, and determine student responses to e-modules teaching. This research method is the development of Research and Development using the ADDIE model which in its implementation uses 5 stages, namely: analysis, design, development, implementation, and evaluation. Limited trial with 50 third-semester students of PGPAUD UNG. Based on the results of the material validation assessment, media experts got score of 98.89% in the